2021
DOI: 10.1111/phn.12899
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid expansion and accessibility to healthcare: The Illinois experience

Abstract: Objective The study examined the impact that the Medicaid expansion in Illinois had upon insurance rates, access to medical care, dental care, pharmaceuticals, and mental‐health counseling between rural and urban counties. Design and Sample A serial cross‐sectional design was used to assess the health perceptions of adults living in Illinois. Measures Survey data were collected in 2012 (n = 6,149) before the Medicaid expansion in Illinois and in 2015 (n = 3,532) after the expansion from rural (n = 4) and urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous work has shown that influenza immunization rates among pregnant women in rural areas of the United States are 6% lower compared to their urban counterparts, 13 with individual or area‐specific challenges in accessing health care like workforce shortages, 14 hospital closures, 15 and having to travel longer distances to receive health care 16,17 as possible reasons for this gap. Insurance status, which is an important predictor of maternal vaccination, 18,19 is also known to vary for urban and rural areas of the United States 20,21 . However, the impact of state policy decisions that influence health access on the urban‐rural disparity in maternal immunization has not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that influenza immunization rates among pregnant women in rural areas of the United States are 6% lower compared to their urban counterparts, 13 with individual or area‐specific challenges in accessing health care like workforce shortages, 14 hospital closures, 15 and having to travel longer distances to receive health care 16,17 as possible reasons for this gap. Insurance status, which is an important predictor of maternal vaccination, 18,19 is also known to vary for urban and rural areas of the United States 20,21 . However, the impact of state policy decisions that influence health access on the urban‐rural disparity in maternal immunization has not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Insurance status, which is an important predictor of maternal vaccination, 18,19 is also known to vary for urban and rural areas of the United States. 20,21 However, the impact of state policy decisions that influence health access on the urban-rural disparity in maternal immunization has not been previously investigated. To address this, we aimed to evaluate the disparity in urban-rural immunization rates among pregnant women by indicators of access to health care, and we examined whether this disparity varied by region of the United States.…”
Section: Introductionmentioning
confidence: 99%